Role of Non-State Actors in National Security - Luitel, Prabhukar (Unity Journal, 2024)
Globalization has elevated the role of non-state actors (NSAs) in national security. This article underscores the need to acknowledge the influence of NSAs on international relations and national security. It discusses the role of NSAs only in democratic states with limited government, excluding the totalitarian and authoritarian states, as they blur the private-public distinction or restrict NSAs. The paper follows a qualitative methodology depending on the scholarly credibility of sources, recency, and relevance. The sources include expert interviews as primary data sources and relevant academic literature and case studies as secondary data sources. It employs thematic analysis for examining the data, enabling a nuanced investigation of the evolving influence of NSAs. The theoretical foundation distinguishes two primary NSA categories: private-sector corporate actors and non-governmental organizations (NGOs), including global social movements (GSMs). Likewise, it investigates how NSAs extend their influence beyond conventional territorial boundaries such as cyber threats, climate threats, and global policy making. The findings highlight the critical role of non-state actors in shaping contemporary national security paradigms through various case studies, offering insights for policymakers.